Prevention of Neurologic Disease with Fasting - Macri, Elizabeth; Azhar, Yusra (Seminars in Neurology, 2022)
Fasting has been widely studied in both prevention and treatment of many neurologic disorders. Some conditions may be prevented with any type of fasting, while some may require a stricter regimen. Fasting reduces weight, fasting blood glucose, and insulin resistance, and favorably alters the gut biome and the immune system. This article discusses various versions of fasting that have been studied as well as the known and theoretical mechanisms of how fasting effects the body and the brain. This article will then review evidence supporting the potential preventive and treatment effects of fasting in specific neurologic disorders including ameliorating the symptoms of Parkinson's disease, improving cognition in Alzheimer's disease, reducing migraine frequency and intensity, and reducing seizure frequency in epilepsy.
Keywords: fasting; prevention; Alzheimer's disease; Parkinson's disease; epilepsy; migraine